Improving the health-promoting properties of fruit and vegetable products - Tomas-Barberan, F. A. (Francisco A.); Gil, M. I. (Maria Isabel) (Woodhead Publishing in food science, technology, and nutrition., 2008)
Consumers are advised to increase fruit and vegetable consumption, but the health effects of increased intake are not fully understood. This important collection brings together information on the health-promoting properties of fruit and vegetables. Introductory chapters provide an overview of fruit and vegetable bioactives and consumer attitudes towards fruit and vegetables. Part two discusses the health effects of fruit and vegetables in relation to specific diseases, including cancer, cardiovascular disease, diabetes, obesity and neurodegenerative diseases. The focus in Part three is on understanding fruit and vegetable phytochemicals. Chapters cover physiological and ecological functions and biosynthesis of health-promoting compounds in fruit and vegetables, rapid analysis of phytochemicals in fruit and vegetables and clinical evidence for biological activity of fruit and vegetable phytochemicals. Part four chapters review the effect of pre- and post-harvest technologies on the health-promoting properties of fruit and vegetables. Topics covered include traditional breeding and modern processing techniques and their effect on fruit and vegetable phytochemicals; genetic manipulation of vegetable crops to alleviate diet-related diseases; agronomy and the nutritional quality of fruit; storage and handling of fruit and vegetables for optimal health-related quality and postharvest enhancement of bioactive compounds in fresh produce using abiotic stresses. The final chapters in Part five look at the nutritional quality of particular fruit and vegetable products, such as fresh-cut fruit and vegetables and organic fruit and vegetables. Improving the health-promoting properties of fruit and vegetable products is a valuable reference for those working in the fresh and processed fruit and vegetable sector of the food industry. Provides an overview of fruit and vegetable bioactivesDiscusses the health effects of fruit and vegetables in relation to specific diseasesReviews the impact of agronomy, post-harvest treatments and processing on the nutritional quality of fresh fruit and vegetables.